ECG Abnormalities in Patients with Acute Exacerbation of Bronchiectasis and Factors Associated with High Probability of Abnormality. (6th July 2021) - Alhamed Alduihi, Fatima
Abstract : Background . Bronchiectasis is an important reason for morbidity and mortality according to the last records that referred to high incidence rate of disease. Cardiovascular problems are common in pulmonary diseases, in general, and it can symptom by ECG abnormalities. The objective of this study was to define the most ECG abnormalities in patients with acute exacerbation of bronchiectasis and to study the correlation between the cardiac disorder and the other risk factors of the exacerbation. Materials and Methods . A prospective single-center observational cohort study was done at Aleppo University Hospital for patients with AEB between October 2017 and September 2018. They were divided into 2 groups (normal ECG vs. abnormal). Patients with COPD, cystic fibrosis, new diagnosis of ischemic accident through the last 6 months of the study, and treatment with macrolides or fluoroquinolones through the last 3 months of the study were excluded. We study the percent of abnormalities through the AEB and the percentage of the most common abnormalities. Results . 67 patients were included in the study (44 males and 23 females) with a mean age of 52.85 ± 21.456 . ECG abnormalities were recorded in 43 patients, and it was more common in men (67.44% of cases). Advanced age and survival state had a statistical significance (p = 0.003, 0.023), respectively, between the 2 groups. Right axis deviation (RAD) is the most common abnormality (23.3%) followed by sinus tachycardia (20.9%), and it is close to T-depression (18.6%). AF was the most common arrhythmia from all recorded arrhythmias (6.98% from all cases). Positive sputum cultures were recorded in 55.8%, and the most common isolated pathogen factor was Pseudomonas aeruginosa . Recurrent pneumonia was seen in 30.2% of all patients with abnormal ECG. We find a high prevalence of ECG abnormalities in patients with Oximetry (90-95%, 39.5%), and the opportunity for abnormalities is equal in the 2 age groups (45–59 and more than 75) that reflexed the possibility of cardiac disorders in any age in patients with AEB. Conclusions . ECG abnormalities are common in AEB, and it can happen in any age and any value of Oximetry. It needs more attention because of the prognosis of the cardiac morbidity.